Risco de doença cardiovascular em mulheres com história de distúrbio hipertensivo da gravidez - Dantas, Edailna Maria de Melo (2013)
OBJECTIVE: Preeclampsia is a disease that can lead to a high maternal and infant morbidity. Worldwide, the incidence of this disease is highly variable and there is no data on this disorder in the Brazilian population. This study aimed at determining incidence and risk factors in the hypertensive disorders during pregnancy in a neighborhood of Natal, in addition to observing the evolution of these disorders one year and five years after delivery. METHODS: Prospective cohort study to assess the outcome of pregnancies of 242 women who became pregnant between 2004-2007 in the neighborhood of Bom Pastor in the city of Natal, state of RN, Brazil. Five years after delivery, there was an active search of thirty-nine (39) women who became pregnant and had a hypertensive disorder during pregnancy and/or pré-eclâmpsia, out of the total of 242 participants in the initial study. We administered a structured questionnaire to obtain basic information about the current clinical situation of patients and occurrences of subsequent pregnancy and presence of hypertensive disorders during pregnancy. We also searched for information on the use of hypotensive drugs and contraceptives. The following characteristics were checked and recorded: a) current weight, b) blood pressure c) body mass index - BMI, and we collected biological samples (blood and urine) for measurement of biochemical parameters and evaluation of microalbuminúria. Finally, we monitored the ambulatory blood pressure (ABP), which uses the method of automatic measurement of heart rate, systolic and diastolic blood pressure and an average of the two for the period of 24 hours. RESULTS: Out of 218 women who completed the study, the incidence of hypertensive disorders was of 16.9% (37 out of 218), while the incidence of preeclampsia was 13.8% (30 of 218). Women with preeclampsia had a BMI (body mass index) averaged of 25.3 (± 4.8) while this ratio in normotensive women was of 23.5 (± 3.7), p = 0.02. The risk of preeclampsia rises with age (OR 1084 p = 0.0034) and with a family history of hypertension (OR 2.6 p = 0.01). The follow-up one year after delivery revealed that 50% of women with hypertensive disorders in pregnancy remained hypertensive. High BMI was also observed after 5 years of delivery. CONCLUSIONS: an elevated BMI, age above 35 years and excessive weight gain during pregnancy were associated with hypertension in the long term in patients with prior preeclampsia. History of preeclampsia increases the risk of chronic hypertension